A MICC Algorithm for Power Quality Improvement Using PV-DSTATCOM - Mishra, Soumya; P. Praveena; Sarin, M. V. (Asian Journal of Electrical Sciences, 2019)
A modified indirect control algorithm is presented in this paper to improve the operation of photovoltaic fed distributed static compensator. This new algorithm overcomes the limitations of direct current control algorithm under non-ideal supply voltage conditions such asswitching notches in source current after compensation, distortions in the reference source current and poor harmonic elimination. The design and performance testing of the presented system has been carried out in MATLAB/Simulink software. Furthermore, the efficacy and robustness of the presented system are validated through experiment.